2019
DOI: 10.1002/capr.12273
|View full text |Cite
|
Sign up to set email alerts
|

Can clinical psychology students benefit from brief and intensive mindfulness training?

Abstract: This pilot study examined the impact of mindfulness training on skills relevant for the well‐being and therapeutic functioning of clinical psychology students. Twenty‐five psychology students took part in an intensive mindfulness training programme, consisting of three 2.5‐hr sessions and one all‐day silent retreat. The students filled out self‐report measures of rumination, emotional reactivity to stress, difficulties with emotion regulation, mindfulness and self‐compassion. They also completed two cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 92 publications
(135 reference statements)
0
8
0
Order By: Relevance
“…More recently, the effects on self-compassion produced by other types of mindfulness-based interventions have been analyzed. For instance, a quasi-experimental research using a Mindfulness for Stress Program with primary care health professionals, 53 a pilot study using an Intensive Mindfulness Training program with clinical psychology students 54 and a single case study using a mindfulness-based mobile intervention with a counselor. 55 Pizutti et al 53 and Schanche et al 54 reported, among other effects, significant improvements in the global levels of self-compassion assessed with the SCS, with the second study also finding improvements in 5 of the 6 SCS subscales (all self-compassion dimensions except common humanity).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the effects on self-compassion produced by other types of mindfulness-based interventions have been analyzed. For instance, a quasi-experimental research using a Mindfulness for Stress Program with primary care health professionals, 53 a pilot study using an Intensive Mindfulness Training program with clinical psychology students 54 and a single case study using a mindfulness-based mobile intervention with a counselor. 55 Pizutti et al 53 and Schanche et al 54 reported, among other effects, significant improvements in the global levels of self-compassion assessed with the SCS, with the second study also finding improvements in 5 of the 6 SCS subscales (all self-compassion dimensions except common humanity).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a quasi-experimental research using a Mindfulness for Stress Program with primary care health professionals, 53 a pilot study using an Intensive Mindfulness Training program with clinical psychology students 54 and a single case study using a mindfulness-based mobile intervention with a counselor. 55 Pizutti et al 53 and Schanche et al 54 reported, among other effects, significant improvements in the global levels of self-compassion assessed with the SCS, with the second study also finding improvements in 5 of the 6 SCS subscales (all self-compassion dimensions except common humanity). The single-case study found that the use of the Calm © app did not generate significant increases in self-compassion, although it did improve levels of burnout and mindfulness.…”
Section: Resultsmentioning
confidence: 99%
“…National psychotherapy associations may foster the well-being of psychotherapists through various means: for example, physical activity, mindfulness-based resilience training, or practicing autogenic training may be recommended. Mindfulness-based resilience training has been found to have a positive impact on psychological well-being in mental health professionals (de Zoysa et al, 2014), to reduce stress in physicians (Schroeder et al, 2016), and to reduce stress reactivity in clinical psychology students (Schanche et al, 2020). The available meta-analyses also suggest that mindfulnessbased training reduces stress levels and anxiety and increases psychological resilience (Cavanagh et al, 2014;Khoury et al, 2013Khoury et al, , 2015.…”
Section: Implications For Practice and Recommendations For National P...mentioning
confidence: 99%
“…In fact, the majority of models tested in this study support stress as a partial, not full, mediator of the relationship between trait mindfulness and cognitive functioning. Other potential mediators could include rumination (Schanche et al, 2020) and attention monitoring (Lindsay & Creswell, 2017). Finally, as discussed above, perceived cognitive functioning is often distinct from objectively measured cognitive performance.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…To date, much of the literature on mindfulness, stress, and cognitive functioning in college students has focused on enhancing cognitive or academic performance through meditation training. For example, several preliminary trials have found positive effects of MBIs offered in college settings on working memory and GRE reading-comprehension scores (Mrazek et al, 2013), retention of course material (Ching et al, 2015), executive control (Schanche et al, 2020), GPA (Napora, 2013), and quiz performance (Calma-Birling & Gurung, 2017). There is also some indication that even brief mindfulness exercises have immediate positive effects on memory performance (Eisenbeck et al, 2018;Lloyd et al, 2016).…”
mentioning
confidence: 99%